Parasites causing disease in wild and cultured fish in Newfoundland - Rasul A. Khan (2009)
This study, based on field and laboratory observations, investigated the role of parasites as the cause of disease outbreaks and mass mortality in wild and cultured fish in Newfoundland over three decades. One ciliated protozoan, Trichodina jadranica (Ciliophora), and Loma branchialis (Microspora) were responsible for mass mortality of cultured fry and fingerling Atlantic cod (Gadus morhua) while a myxozoan, Tetracapsuloides bryosalmonae, and plerocercoids of a cestode, Diphyllobothrium dendriticum, caused a die-off of hatcheryreared Arctic charr (Salvelinus alpinus) and rainbow trout (Oncorhynchus mykiss) respectively after transfer to outdoor cages. A hematophagous copepod, Lernaeocera branchialis, was associated with mortality of wild Atlantic cod both in the laboratory and possibly in the field. One additional parasite, a coccidian, Goussia caseosa, caused lesions in the swim bladder of the roughhead grenadier, Macrourus berglax, a deep-sea fish. It is surmised that parasites have played a major role in mortality of both wild and cultured fish in Newfoundland. Recommendations are made to prevent potential die-offs in cultured fish. Í rannsókninni, sem byggir á rannsóknarvinnu ásamt reynslugögnum úr fiskeldinu, var kannaður hlutur sníkjudýra í sjúdómsfaröldrum og afföllum villi- og eldisfiska á Nýfundnalandi í þrjá áratugi. Tvær tegundir frumdýra (Protozoa), Trichodina jadranica (bifdýr) og Loma branchialis (Microspora), ollu stórfelldum afföllum í þorskseiðum í eldi. Eftir flutning fiska í sjókvíar, olli smásær fjölfrumungur, Tetracapsuloides bryosalmonae (Myxozoa), afföllum í bleikju (Salvelinus alpinus) og lirfustig bandormsins Diphyllobothrium dendriticum olli dauða regnbogasilunga (Oncorhyncus mykiss). Blóðsníkillinn Lernaeocera branchialis (krabbadýr) tengdist afföllum villiþorska, bæði við tilraunaaðstæður svo og í rauneldi. Auk þessa olli hnísildýrið Goussia caseosa (Coccidia) skemmdum í sundmaga snarphala(Macrourus berglax), sem er djúpsjávarfiskur. Leiddar eru líkur að því að sníkjudýr eigi stóran ...